2019
DOI: 10.1016/j.jgr.2017.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effect of black ginseng extract against oxidative stress-induced cellular damages in mouse hepatocytes

Abstract: Background Oxidative stress induces the production of reactive oxygen species (ROS), which play important causative roles in various pathological conditions. Black ginseng (BG), a type of steam-processed ginseng, has drawn significant attention due to its biological activity, and is more potent than white ginseng (WG) or red ginseng (RG). Methods We evaluated the protective effects of BG extract (BGE) against oxidative stress-induced cellular damage, in comparison with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 33 publications
2
15
0
1
Order By: Relevance
“…Correspondingly, the antioxidant activities (DPPH, ABTs, and FRAP assays) of ginseng-SDF were significantly higher than the tropical fruits as sapodilla, dragon fruit and mamoncillo, cocoa coproducts, and cereals SDF (Can-Cauich et al, 2017;Guo & Beta, 2013;Martínez et al, 2012aMartínez et al, , 2012b. According to the report of Da Silva et al (2014), the TPC of fruits can be divided into increase the release of polyphenols (Choudhry et al, 2019). Our research also proved that some polyphenols remain in ginseng residue.…”
Section: Tpc Ginsenoside Components and Antioxidant Activitysupporting
confidence: 57%
“…Correspondingly, the antioxidant activities (DPPH, ABTs, and FRAP assays) of ginseng-SDF were significantly higher than the tropical fruits as sapodilla, dragon fruit and mamoncillo, cocoa coproducts, and cereals SDF (Can-Cauich et al, 2017;Guo & Beta, 2013;Martínez et al, 2012aMartínez et al, , 2012b. According to the report of Da Silva et al (2014), the TPC of fruits can be divided into increase the release of polyphenols (Choudhry et al, 2019). Our research also proved that some polyphenols remain in ginseng residue.…”
Section: Tpc Ginsenoside Components and Antioxidant Activitysupporting
confidence: 57%
“…It has its name originated from "Jen Sheng" a Chinese word meaning "man herb" due to the shape of the root which is human like shape [ 237 ], “ panax” a Greek word meaning "all heal", this shows that it can cure all kind of diseases [ 238 ]. The commonly studied Ginseng are "Panax ginseng", "Panax quinquefolium" and Panax notoginseng [ 239 ] exhibiting a lot of biological effects [ 237 ]. The active constituents of ginseng called "ginsenosides" shows neuroprotective effects and enhances memory [ 240 ] (Scheme 5 ).…”
Section: Role Of Chinese Nutraceuticals In Tau Neurodegenrative Diseamentioning
confidence: 99%
“…Rg1 also reduces Aβ formation and decreases hyperphosphorylated tau. One of the major treatments of AD is a principal Acetylcholine (ACh) neurotransmitters in which cognition and memory process is reduced in AD [ 237 ]. This neurotransmitter is terminated by an enzyme known as Acetylcholinesterase (AChE), and butyryl cholinesterase (BChE), which is present in patients with AD as well as inhibiting of choline acetyltransferase (ChAT) activity (an enzyme responsible for ACh metabolism) [ 243 ].Studies have shown that Rb1,Rb2, Rc,Re,Rg1 and Rg3 have a reducing property on AChE and BChE [ 243 , 244 ].…”
Section: Role Of Chinese Nutraceuticals In Tau Neurodegenrative Diseamentioning
confidence: 99%
“…Гинзенозид Rg1, например, в первичной культуре изолированных нейронов черной субстанции (продуцирующих дофамин) крыс обнаруживает отчетливые протекторные свойства при оксидантном стрессе, вызванном митохондриальным токсином ротеноном [16]. Оральное применение экстрактов женьшеня и родиолы предупреждало токсическое действие четыреххлористого углерода на печеночную ткань крыс и мышей с повышением активности антиоксидантного фермента супероксиддисмутазы и ограничением накопления малонового диальдегида как одного из продуктов перекисного окисления липидов [17,18].…”
Section: антистрессорное действие фитоадаптогеновunclassified